Community, creativity and piracy: a triadic approach towards understanding music streaming adoption among Indian audiences. (27th July 2021) - Pillai, Akhil; Namadev, K.; Kumar, Pranith; Suresh, Kalyani
Online music streaming is relatively fresh in India but there are a considerable number of users and downloads since its arrival in the country. This research is an attempt to address the literature gap in understanding music streaming purchase vs. piracy intention among Indian consumers. The results of the field study involving 500 respondents suggest that music streaming services (MSSs) that incorporate features that facilitate individual creativity and community building contributes towards the ease of use and usefulness of the system. MSSs that integrate features that advance creativity facilitation help users derive a sense of ease of use and enjoyment. Features that also contribute towards community facilitation along with enjoyment lead to intention to subscribe to MSSs. The results of the study also show a link between enjoyment and a reduction in unauthorised downloading intention. A convincing value-proposition for a pronounced user experience is imperative for a successful business model.